The emergence of romanticism - Riasanovsky, Nicholas V. (Nicholas Valentine), 1923-2011 (Oxford University Press, 1992)
Viewed as one of the most tumultuous, momentous movements in the history of world literature, Romanticism and its origins have long been studied by literary critics. In this book, Nicholas Riasanovksy, primarily known as an eminent historian of Russia, offers a refreshing and appealing new interpretation of Romanticism's origins, goals, and influence. The original surge of Romantic thought occurred in England and Germany in the middle to late 1790s, and within a decade had spent itself. Riasanovsky focuses on the explosion of the Romantic impulse, and searches for the origins of the revolutionary vision that made the early Romantic poets in England and Germany take an entirely different view of the world. Pairing two British authors (Wordsworth and Coleridge) with three German authors (Novalis, Friedrich Schlegel, and Wackenroder), Riasanovsky demonstrates that, for all the cultural differences between them, they represent variations on the same "emergence." Essentially, all five were obsessed with the problem of their eternal striving and inability to reach their own goals. All five abandoned the Romantic ideology within a decade and, having supported the goals of the French Revolution in the 1790s, retreated into political conservatism or religious orthodoxy. Riasanovsky identifies the heart of Romanticism as being the creature of a pantheistic religious culture. He stresses that Romanticism was produced only by Western Christian civilization, with its unique view of humankind's relationship to God. The Romantics' frantic and heroic striving for unreachable goals mirrors Christian beliefs in human inability to adequately address God, speak to God, or praise God. Further, Riasanovsky argues that Romantic thought had important political implications, playing a key role in the rise of nationalism in Europe. Offering a historical examination of an area often limited to literary analysis, this book gracefully makes a larger historical statement about the nature and centrality of European Romanticism. Not limited to the cultural historian and the literary critic, The Emergence of Romanticism also makes available to the general reader a jargon-free look at the heady days of Romanticism.